(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aimed to design a test of pre-writing skills for public kindergartens in Baghdad city. The test consisted of (25) items applied on a sample of (150) kindergarteners to identify these skills as well as to identify the significant difference between male and female children and if there is a difference between pre-school children and kindergarteners. The results showed the presence of pre-writing skills with a high degree in kindergarten children. The differences were clear in these skills between male and female children and those in pre-school than those in kindergartens. The researcher suggested a number of recommendations and proposals.